A Serious Game ("Fight With Virus") for Preventing COVID-19 Health Rumors: Development and Experimental Study - Shuo Xiong; Long Zuo; Qiwei Chen; Zhang Zeliang; Mohd Nor Akmal Khalid (JMIR Publications, 2024)
BackgroundHealth rumors arbitrarily spread in mainstream social media on the internet. Health rumors emerged in China during the outbreak of COVID-19 in early 2020. Many midelders/elders (age over 40 years) who lived in Wuhan believed these rumors. ObjectiveThis study focused on designing a serious game as an experimental program to prevent and control health rumors. The focus of the study was explicitly on the context of the social networking service for midelders/elders. MethodsThis research involved 2 major parts: adopting the Transmission Control Protocol model for games and then, based on the model, designing a game named "Fight With Virus" as an experimental platform and developing a cognitive questionnaire with a 5-point Likert scale. The relevant variables for this experimental study were defined, and 10 hypotheses were proposed and tested with an empirical study. In total, 200 participants were selected for the experiments. By collecting relevant data in the experiments, we conducted statistical observations and comparative analysis to test whether the experimental hypotheses could be proved. ResultsWe noted that compared to traditional media, serious games are more capable of inspiring interest in research participants toward their understanding of the knowledge and learning of health commonsense. In judging and recognizing the COVID-19 health rumor, the test group that used game education had a stronger ability regarding identification of the rumor and a higher accuracy rate of identification. Results showed that the more educated midelders/elders are, the more effective they are at using serious games. ConclusionsCompared to traditional media, serious games can effectively improve midelders'/elders' cognitive abilities while they face a health rumor. The gameplay effect is related to the individual's age and educational background, while income and gender have no impact.